Identifying mutations in Tunisian families with retinal dystrophy - Habibi, Imen (Sci Rep, 2016)
Retinal dystrophies (RD) are a rare genetic disorder with high genetic heterogeneity. This study aimed at identifying disease-causing variants in fifteen consanguineous Tunisian families. Full ophthalmic examination was performed. Index patients were subjected to IROme analysis or whole exome sequencing followed by homozygosity mapping. All detected variations were confirmed by direct Sanger sequencing. Mutation analysis in our patients revealed two compound heterozygous mutations p.(R91W);(V172D) in RPE65, and five novel homozygous mutations: p.R765C in CNGB1, p.H337R in PDE6B, splice site variant c.1129-2A > G and c.678_681delGAAG in FAM161A and c.1133 + 3_1133 + 6delAAGT in CERKL. The latter mutation impacts pre-mRNA splicing of CERKL. The other changes detected were six previously reported mutations in CNGB3 (p.R203*), ABCA4 (p.W782*), NR2E3 (p.R311Q), RPE65 (p.H182Y), PROM1 (c.1354dupT) and EYS (c.5928-2A > G). Segregation analysis in each family showed that all affected individuals were homozygotes and unaffected individuals were either heterozygote carriers or homozygous wild type allele. These results confirm the involvement of a large number of genes in RD in the Tunisian population.